Learning Planning and Organizing as Determinants of Kitab Kuning Learning Effectiveness - Mustaqim; Ulva Rahmi (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to analyze the influence of learning planning and organization on the effectiveness of kitab kuning (classical Islamic text) learning at Pondok Pesantren Madinatul Munawwarah, Bukittinggi City. The research employs a quantitative approach with an explanatory research design. The population includes teachers of kitab kuning and students (santri) directly involved in the learning process, with samples selected through purposive sampling techniques. Data were collected using questionnaires and documentation, and analyzed using multiple linear regression to determine the relationships among variables. The results indicate that learning planning has a significant effect on learning effectiveness, as reflected in teacher preparedness, clarity of objectives, and the suitability of learning materials and methods. Furthermore, learning organization also shows a significant influence through effective coordination among educators, time management, and the utilization of facilities and infrastructure. Simultaneously, both variables contribute positively to enhancing the effectiveness of kitab kuning learning. The findings highlight the importance of well-structured planning and organization as strategic foundations for achieving effective kitab kuning learning in Islamic boarding schools.